Land ownership and land use development. The integration of past, present, and future in spatial planning and land management policies. - (:unkn) unknown (vdf Hochschulverl., 2017)
Across Europe, land is constantly the subject of enormous and widely varied pressures. The land we have is shrinking in area due to numerous reasons, including those that are directly related to climate change and migration. In fact all disciplines that have responsibilities for the husbandry use, management, and administration of the land are forced to address the problems of how to plan and how to utilise this increasingly valuable resource. The papers contained within this book emerge from two symposia held in 2014 and 2015, which now have been arranged along four general themes reflecting the multi-disciplinary nature of the disciplines concerned with land. The first part is dedicated to the interpretation of key terms in their context and the dissimilar conceptual approaches in the governance of different states. It is followed by papers that identify the process of decision-taking: how to organize and co-operate. One large section addresses the identification of land pattern changes and the reason for it. The papers in the final cluster deal with the general theme of strategies and measures used to steer future evolution in land policies. The publication addresses various needs that have to be balanced: the tasks of living space in the face of societal and demographic changes, infrastructure supply, challenges of an increasingly urbanised region, food production, "green energy", natural hazards, habitats and cultural landscapes protection.
Keywords: Raumplanung; Regionalentwicklung; Bodennutzung; Flächennutzung; Siedlungsentwicklung; Kulturlandschaft; Landschaftsschutz; Stadtentwicklung; Stadterneuerung; Biomasse; Ländlicher Raum; Verstädterung; Bodenpolitik; Bodenwert; Kataster; Landnutzung; Bodenmanagement; Landmanagement; Nationalpark; Hochwasservorsorge; Visualisierung; 3D-Modell